ESG Performance, Corporate Governance, and Firm Value: Evidence from Global Oil and Gas Companies - Agung Nurhananto Putro; Nur Dhani Hendranastiti (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Global oil and gas companies face increasing pressure from the energy transition and rising ESG expectations, requiring firm value assessment beyond traditional financial indicators to include environmental, social, and governance (ESG) performance and corporate governance quality. Objective: This study examines the effect of ESG performance, board size, board independence, director busyness, board diversity, and ownership concentration on firm value, with financial performance as a mediating variable in global oil and gas companies during 2020–2024. Methods: A quantitative panel data approach is employed, with firm value measured using price-to-book value (PBV). The analysis applies a Fixed Effects Model with Driscoll–Kraay standard errors, bootstrap mediation analysis, and robustness checks separating U.S. and non-U.S. firms. Results: ESG performance has a positive but only marginally significant effect on firm value, which becomes insignificant after controlling for financial performance. Financial performance does not mediate the ESG–firm value relationship. Among governance variables, only board size has a significant positive effect on firm value, while board independence, director busyness, board diversity, and ownership concentration are not statistically significant. Robustness tests confirm overall consistency, with observable contextual differences across regions. Conclusion: Firm value in global oil and gas companies is primarily driven by board size as a proxy for monitoring capacity and strategic resources, rather than ESG performance or other governance mechanisms, emphasizing the importance of aligning governance structure with operational efficiency and long-term value creation.